2018
DOI: 10.1021/acs.jpcc.7b12296
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Tracer Diffusion in Amorphous LixSi for Low Li Concentrations

Abstract: Li tracer self-diffusion was studied in amorphous lithium−silicon compounds which are important as negative electrodes in Li-ion batteries. Experiments were done on Li x Si/ 6 Li x Si (Li x Si, x ∼ 0.02 and x ∼ 0.06) thin-film heterostructures using secondary ion mass spectrometry. The diffusivities follow the Arrhenius law in the temperature range between 140 and 325 °C, both with an activation energy of (1.42 ± 0.03) eV, while the Li-richer samples show 1 order of magnitude higher diffusivities. A trap-limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 50 publications
9
36
0
Order By: Relevance
“…There is the distinctive pathway for minimizing the concentration gradient, Li + mass transport from silicon to graphite due to the internal redox reaction. During CV charge, this pathway delays the end of CV charging time because Li + diffusivity in silicon is 2 orders lower than that in graphite [33,34]. Consequently, the time for CV charge increases, and then delithiated cathode experiences high cut-off voltage during extended CV charging time.…”
Section: Crosstalk Of LI + Between Silicon and Graphitementioning
confidence: 99%
“…There is the distinctive pathway for minimizing the concentration gradient, Li + mass transport from silicon to graphite due to the internal redox reaction. During CV charge, this pathway delays the end of CV charging time because Li + diffusivity in silicon is 2 orders lower than that in graphite [33,34]. Consequently, the time for CV charge increases, and then delithiated cathode experiences high cut-off voltage during extended CV charging time.…”
Section: Crosstalk Of LI + Between Silicon and Graphitementioning
confidence: 99%
“…51 Further, systematic diffusion studies in Li x Si revealed that Li diffusivities are significantly enhanced with increasing Li content. 50 Consequently, as a perspective, the application of the NR methodology to determine in situ the rate determining step of Li permeation through Li x Si alloys and their interfaces to, e.g., different oxide based solid electrolyte materials is desirable in the context of battery applications.…”
Section: Resultsmentioning
confidence: 99%
“…[ 141 144 ]: cm s 2019 [ 145 ] Activation energy ( ) 0.5 − 0.8 eV N/A 2019 [ 145 ] ( ) 1.21-1.46 eV Exp. [ 146 ]: 1.38 − 1.46 eV 2020 [ 147 ] Solid electrolytes Amorphous- 0.55 eV Exp. [ 148 ]: 0.58 eV 2017 [ 149 ] 0.16 eV Exp.…”
Section: Applications To Industrymentioning
confidence: 99%